A composite polyanionic sodium ferrous sulfate positive electrode material, a preparation method thereof, and a sodium ion battery containing the positive electrode material
Patent Information
- Application Number
- CN202210419001.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-04-20
AI Technical Summary
固相球磨前需对FeSO4·nH2O原材料在真空或无氧氛围下高温(300℃左右)长时间(10-12h)脱水制备无水FeSO4,但结晶水脱出后会营造出潮湿的环境,导致Fe2+极易被氧化为Fe3+,致使所制备的硫酸亚铁钠正极材料体相纯度低,脱嵌Na+能力弱
[0050](1)本发明中,利用硫酸盐易溶于水的特性,将其溶于水中,通过喷雾干燥得到粉末状原子级均匀混合的双组分金属盐混合物,操作简单、可控、耗时短。
Smart Images

Figure CN116960281B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathode materials for sodium-ion batteries, specifically to a composite polyanionic sodium ferrous sulfate cathode material, its preparation method, and a sodium-ion battery containing this cathode material. Background Technology
[0002] Energy and the environment are the foundation upon which human society depends for survival and development. While renewable and clean energy systems, such as wind, tidal, geothermal, and solar energy, have alleviated the two major global problems of energy shortage and environmental pollution to some extent, these clean energy sources exhibit inherent intermittent characteristics due to weather, geographical location, and climate conditions, which is detrimental to the efficient operation of power grids. Distributed clean energy sites combined with large-scale power storage and conversion systems represent one of the main directions for future energy development. Rechargeable batteries, with their adjustable storage capacity, portability, and high degree of modular integration, meet the current demands of energy storage technology for low cost, high efficiency, large scale, and long lifespan, and therefore have a very broad application prospect.
[0003] Since Sony commercialized lithium-ion batteries (LIBs) in the 1990s, years of technological updates and equipment improvements have led to their successful application in portable electronic devices, electric vehicles, and energy storage grids. However, global lithium resources are scarce (0.0065 wt% in the Earth's crust), making it difficult to support the ever-growing market demand. Furthermore, significant safety hazards such as thermal runaway and combustion limit the long-term large-scale development and application of lithium-ion batteries in energy storage and conversion. Against this backdrop, the development of Na+ batteries, which share similar working principles, manufacturing processes, and engineering mass production procedures with lithium-ion batteries but offer significant advantages in resources, cost, and safety, is crucial. + The development of sodium-ion batteries, which are carriers, complementing lithium-ion batteries, and even completely replacing lithium-ion batteries, is the inevitable path for large-scale energy storage technology.
[0004] because Comparison The large ionic radius of sodium-ion batteries leads to extremely slow transport kinetics at the electrode material interface and in the bulk phase, accompanied by significant volume effects and severe electrode structural damage. This severely restricts the development and commercialization of high-performance sodium-ion batteries. Therefore, researching cathode materials, which determine the energy density and power density of the entire sodium-ion battery system, is one of the main research directions for promoting the large-scale application of sodium-ion batteries. Currently, the cathode material systems that have attracted much attention mainly include: transition metal layered oxides, Prussian blue analogs, and polyanionic compounds. Among them, transition metal layered oxides face problems such as poor air stability, low operating voltage platform, significant bulk phase changes and complex phase transitions during electrode reactions; Prussian blue analogs possess open three-dimensional Na+... + The channel exhibits good structural stability and rate performance, but the presence of difficult-to-remove water of crystallization within its crystal structure leads to low cycle efficiency and a tendency for transition metal dissolution. Polyanionic cathode materials, particularly sodium ferrous sulfate cathode materials with an alluaudite crystal structure, possess the highest reported charge-discharge voltage plateau to date (3.8V vs. Na). + The open three-dimensional framework, high thermal stability, good rate performance and excellent cycle performance, safety and non-toxicity, and low cost of this type of material make it a potential market value and application in the fields of energy storage and micro electric vehicle technology.
[0005] In 2014, Barpanda et al. (Nature Communications, 2014, 5(1): 4358.) first reported that Na2Fe2(SO4)3 type sulfate cathode materials have reversible Na insertion / extraction deintercalation. + The properties of [SO4] opened up a new field of research on polyanionic sulfate cathode materials. Since then, many [SO4]-based materials have been developed. 2-Strongly inductively coupled cathode materials have been extensively studied and reported. Research focuses on two aspects: optimizing the bulk purity of sodium ferrous sulfate cathode materials by selectively controlling the ratio of raw materials Na2SO4 and FeSO4, and improving the electronic conductivity of the materials by incorporating carbon matrix. For example, Oyama's team (CHEMELECTROCHEM, 2015, 2(7):1019-1023) found that the types and contents of impurity phases (including Fe2O3, Na6Fe(SO4)4, α-FeSO4, β-FeSO4, etc.) in the prepared sodium ferrous sulfate cathode materials varied by controlling the ratio of Na2SO4-FeSO4. DFT theoretical calculations combined with Mössbauer spectroscopy analysis confirmed that the impurity phase in sodium ferrous sulfate cathode material mainly originates from a small amount of unreacted FeSO4, rather than the cathode material obtained by stoichiometry which has the highest bulk purity. That is, a slight excess of sodium salt can significantly reduce the formation of impurity phases during the synthesis process (Journal of Materials Chemistry A, 2019, 7(21): 13197-13204.). In addition, research teams such as Yao (Journal of Energy Chemistry, 2020, 50: 387-394.), Wang (Journal of Materials Chemistry A, 2018, 6(10): 4354-4364.), Cao (Journal of Energy Chemistry, 2021, 54: 564-570.), and Meng (Journal of Materials Chemistry A, 2016, 4(5): 1624-1631.) have achieved significant improvements in the cycle life, rate capability, and stability of sodium ferrous sulfate cathode materials by introducing different conductive matrices into the material system.
[0006] However, currently, the strong electronegativity [SO4] 2- The preparation of sodium ferrous sulfate cathode materials mostly employs a low-temperature solid-state ball milling process, followed by low-temperature sintering under an inert atmosphere. Before solid-state ball milling, the FeSO4·nH2O raw material needs to be dehydrated at high temperature (around 300℃) for a long time (10-12 hours) in a vacuum or oxygen-free atmosphere to prepare anhydrous FeSO4. However, the removal of crystal water creates a humid environment, leading to Fe… 2+ It is easily oxidized to Fe 3+ This resulted in low bulk purity of the prepared sodium ferrous sulfate cathode material, and deintercalation / intercalation of Na... + The sodium ferrous sulfate cathode material has weak performance. Therefore, there is an urgent need for a new preparation process to improve the bulk purity and conductivity of the sodium ferrous sulfate cathode material, enhance its overall electrochemical performance such as reversible charge-discharge specific capacity, rate performance, and cycle stability, and accelerate the development of sodium-ion batteries. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention provides a composite polyanionic sodium ferrous sulfate cathode material, its preparation method, and a sodium-ion battery containing this cathode material. The preparation method is simple to operate, easy to control, and environmentally friendly. The composite polyanionic sodium ferrous sulfate cathode material uses two sulfates and a carbon matrix as raw materials, employing a spray-drying coupled solid-phase mixing method. Specifically, firstly, a powdered, atomically homogeneous mixture of two metal salts is obtained through spray drying. Then, the spray-dried two-component metal salt mixture powder is thoroughly mixed with the carbon matrix through solid-phase mixing to enhance the interaction between the three components. Finally, a pyrolysis reaction process yields a composite polyanionic sodium ferrous sulfate cathode material with excellent overall electrochemical performance, suitable for sodium-ion batteries.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing a composite polyanionic sodium ferrous sulfate cathode material, particularly a method coupling spray drying with solid-phase mixing and low-temperature pyrolysis, comprising the following steps:
[0010] S1: Dissolve sodium sulfate and ferrous sulfate evenly in water, add an antioxidant, and then sonicate to obtain a mixed solution;
[0011] S2: The mixed solution obtained in step S1 is spray-dried to obtain a solid powder;
[0012] S3: The solid powder obtained in step S2 is mixed with the carbon matrix material through solid-phase mixing to obtain the cathode material precursor;
[0013] S4: The cathode material precursor obtained in step S3 is subjected to high-temperature pyrolysis under oxygen-free conditions to obtain a composite polyanionic sodium ferrous sulfate cathode material.
[0014] According to an embodiment of the present invention, in step S1, the ferrous sulfate is selected from ferrous sulfate or its crystalline hydrate. Preferably, the crystalline hydrate of ferrous sulfate is FeSO4·nH2O, where n is selected from 1 to 7, for example, the crystalline hydrate of ferrous sulfate is at least one of FeSO4·7H2O, FeSO4·4H2O, and FeSO4·H2O.
[0015] According to an embodiment of the present invention, in step S1, Fe in the mixed solution 2+ The concentration is 0.001-0.4 kg / L, for example, 0.1-0.3 kg / L.
[0016] According to an embodiment of the present invention, in step S1, Na in the mixed solution + Fe2+ and SO4 2- The molar ratio is (2-6):(1-5):(2-8), for example, 4:3:5, 2:2:3, 2:1:1, 6:5:8.
[0017] According to an embodiment of the present invention, in step S1, the antioxidant is selected from at least one of ascorbic acid and its salts, isoascorbic acid and its salts.
[0018] According to an embodiment of the present invention, the molar ratio of antioxidant to ferrous sulfate in step S1 is (0.01-0.5):1, for example, 0.1:1.
[0019] According to an embodiment of the invention, the ultrasonic treatment is performed at room temperature, for example at 10-40°C, or for example at 20-35°C.
[0020] Preferably, the present invention does not specifically limit the time of the ultrasonic treatment, as long as a mixed solution can be obtained. For example, the ultrasonic treatment time is 10-60 minutes, for example, 30 minutes.
[0021] According to an embodiment of the present invention, in step S1, the mixed solution is blue-green.
[0022] According to an embodiment of the present invention, in step S2, the outlet temperature of the spray dryer is 100-150°C.
[0023] According to an embodiment of the present invention, in step S2, during the spray drying process, the feed rate of the mixed solution is 200-2000 mL / h.
[0024] According to an embodiment of the present invention, in step S2, spray drying can be performed using spray drying equipment known in the art.
[0025] According to an embodiment of the present invention, in step S2, the solid powder is preferably white, and the Na and Fe metal salts in the solid powder are highly dispersed at the atomic level.
[0026] According to an embodiment of the present invention, in step S3, the carbon matrix material is preferably inorganic carbon. Preferably, the inorganic carbon is selected from, but not limited to, at least one of multi-walled carbon nanotubes, acetylene black, Ketjen black, graphene, etc.
[0027] According to an embodiment of the present invention, in step S3, the carbon matrix material accounts for 1-10 wt% of the total mass of the cathode material precursor, for example, 3-5 wt%.
[0028] According to an embodiment of the present invention, in step S3, the solid-phase mixing process can be performed using solid-phase mixing equipment known in the art, such as high-speed mixers, ball mills, three-dimensional mixers, etc. Exemplarily, the solid-phase mixing process can be ball milling, for example, using zirconia balls in a ball mill for ball milling.
[0029] Preferably, the mass ratio of the zirconium oxide spheres to the cathode material precursor is (1-10):1, for example, 5:1.
[0030] Preferably, the conditions for ball milling include: a ball milling time of 1-10 hours, for example, 6 hours; and a ball milling speed of 200-800 rpm, for example, 500 rpm.
[0031] According to an embodiment of the present invention, the cathode material precursor is a black powdery solid. In the present invention, in the cathode material precursor obtained by solid-phase mixing treatment, the solid powder of step S2 is uniformly mixed with the carbon matrix material.
[0032] According to an embodiment of the present invention, in step S4, the conditions for high-temperature pyrolysis include: pyrolysis at a pyrolysis temperature of 350-400°C for 12-24 hours, for example, pyrolysis at 350°C for 12 hours.
[0033] Preferably, a heating treatment is required before the high-temperature pyrolysis. Further, the heating treatment includes heating to the pyrolysis temperature at a heating rate of 1-5°C / min, for example, a heating rate of 2°C / min.
[0034] According to an embodiment of the present invention, in step S4, the oxygen-free condition is an inert atmosphere. Preferably, the inert atmosphere can be an inert gas known in the art, such as nitrogen.
[0035] The inventors discovered that, because FeSO4 in the raw material readily absorbs water to form FeSO4·nH2O, existing known low-temperature solid-phase methods require pre-dehydration of FeSO4·nH2O in the raw material. This dehydration process is often very demanding, and Fe... 2+ It is easily oxidized to Fe 3+ This leads to the deintercalation and deintercalation of Na in the resulting cathode material. +The mixing capacity is reduced; moreover, it is difficult to achieve atomic-level complete and uniform mixing of FeSO4 and Na2SO4 during ball milling alone. This invention uses FeSO4·nH2O and Na2SO4 as raw materials and an inorganic carbon matrix material as the carbon source. First, spray drying technology is used to transform the aqueous solution of the two metal salts into a powdered, atomically uniformly mixed two-component metal salt mixture. This achieves atomic-level mixing of the two metal salts and simultaneously realizes the rapid dehydration of FeSO4·nH2O. Furthermore, spray drying quickly removes water molecules from the working environment, preventing the formation of a humid atmosphere that oxidizes Fe. 2+ Furthermore, it can lower the temperature during dehydration, thereby avoiding the formation of basic ferric sulfate. Subsequently, the inorganic carbon matrix material and the spray-dried binary metal salt powder are completely mixed through solid-phase mixing treatment. This not only enhances the interaction between the carbon source and the binary metal salt powder, but also avoids the problem that the inorganic carbon matrix material is insoluble in water, making it impossible to accurately control the carbon doping amount through spray drying. This results in a cathode material precursor with all three components coexisting uniformly. Finally, the cathode material precursor is pyrolyzed to obtain the cathode material of the present invention. The cathode material prepared by the method of the present invention exhibits excellent comprehensive electrochemical performance and is suitable for sodium-ion batteries.
[0036] The present invention also provides a composite polyanionic sodium ferrous sulfate cathode material obtained by the above preparation method.
[0037] According to an embodiment of the present invention, the composite polyanionic sodium ferrous sulfate cathode material comprises an active material and a carbon matrix material, wherein the molecular formula of the active material is Na. x Fe y (SO4) z , where x+2y=2z, and the ratio of x:y:z is (2-6):(1-5):(2-8).
[0038] According to an embodiment of the present invention, the carbon matrix material in the cathode material has a mass fraction of 1-10 wt%, for example, 5-10 wt% or 7-8 wt%.
[0039] According to an embodiment of the present invention, the ratio of x:y:z in the molecular formula of the active substance is, for example, 4:3:5, 2:2:3, 2:1:2, or 6:5:8.
[0040] According to an embodiment of the present invention, in the positive electrode material, the active material is uniformly distributed in the carbon matrix material, such as... Figure 1 As shown.
[0041] According to an embodiment of the present invention, the composite polyanionic sodium ferrous sulfate cathode material has the basic characteristics of... Figure 6 The characteristic XRD diffraction peaks shown in Figure a are as follows.
[0042] The present invention also provides a positive electrode sheet, wherein the positive electrode sheet comprises the above-mentioned positive electrode material.
[0043] The present invention also provides the application of the above-mentioned positive electrode material or positive electrode sheet in sodium-ion batteries.
[0044] The present invention also provides a sodium-ion battery, wherein the sodium-ion battery comprises the above-mentioned positive electrode material or positive electrode sheet.
[0045] According to an embodiment of the present invention, the first-cycle discharge specific capacity of the sodium-ion battery is greater than 60 mAh g. -1 Preferably 60-120mAh g -1 For example, 87.45mAh g -1 82.28mAh g -1 79.63mAh g -1 65.09mAh g -1 .
[0046] According to an embodiment of the present invention, the sodium-ion battery capacity retention rate is not less than 90%, for example, 90-100%.
[0047] According to an embodiment of the present invention, the sodium-ion battery has a cycle life of not less than 200 cycles, for example, 200-5000 cycles.
[0048] Exemplarily, the sodium-ion battery retains 98.76% or 100% of its capacity after 200 cycles. According to an embodiment of the invention, the sodium-ion battery exhibits high-rate charge-discharge performance, preferably with a discharge specific capacity greater than 38 mAh g⁻¹ under 5C charge-discharge conditions. -1 .
[0049] Beneficial effects:
[0050] (1) In this invention, the property that sulfate is easily soluble in water is utilized to dissolve it in water and obtain a powdered atomically uniform two-component metal salt mixture by spray drying. The operation is simple, controllable and time-saving.
[0051] (2) The anhydrous FeSO4 used in the existing low-temperature solid-phase ball milling method is obtained by pre-dehydration treatment of FeSO4·nH2O. Due to the uncontrollable dehydration process, some Fe2O3 is lost after dehydration. 2+ It will inevitably be oxidized to Fe. 3+ Furthermore, the reproducibility between different batches is extremely poor, resulting in significant differences in the performance of the prepared cathode materials. However, this invention allows for precise control of Na, Fe, and SO42-. 2- The molar ratio among the three components ensures high operational repeatability.
[0052] (3) This invention addresses the problems of poor water solubility of carbon matrix materials, their tendency to agglomerate in aqueous solutions, and the severe carbon source retention during spray drying, which makes it difficult to control the amount of carbon matrix material in the cathode material. This invention utilizes solid-phase mixing treatment to enhance the interaction between the two-component metal salt mixture obtained after spray drying and the carbon matrix material, greatly promoting the Na… + Simultaneous transfer of charge carriers and electrons enhances the electrochemical performance of cathode materials. Attached Figure Description
[0053] Figure 1 This is a SEM image of the cathode material obtained in Example 1 of the present invention;
[0054] Figure 2 This is a SEM image of the cathode material obtained in Comparative Example 1 of this invention;
[0055] Figure 3 This is a SEM image of the cathode material obtained in Comparative Example 2 of this invention;
[0056] Figure 4 This is a SEM image of the cathode material obtained in Comparative Example 3 of this invention;
[0057] Figure 5 This is a SEM image of the cathode material obtained in Comparative Example 4 of this invention;
[0058] Figure 6 This is the XRD pattern of the cathode material obtained in Example 1 of the present invention;
[0059] Figure 7 This is the XRD pattern of the cathode material obtained in Comparative Example 1 of this invention;
[0060] Figure 8 This is the XRD pattern of the cathode material obtained in Comparative Example 2 of this invention;
[0061] Figure 9 This is the XRD pattern of the cathode material obtained in Comparative Example 3 of this invention;
[0062] Figure 10 This is the XRD pattern of the cathode material obtained in Comparative Example 4 of this invention;
[0063] Figure 11 This is the first charge-discharge curve of the cathode material obtained in Example 1 of the present invention at 0.05C;
[0064] Figure 12 This is a graph showing the first charge-discharge curve of the cathode material obtained in Comparative Example 1 of this invention at 0.05C.
[0065] Figure 13 This is the first charge-discharge curve of the cathode material obtained in Comparative Example 2 of the present invention at 0.05C;
[0066] Figure 14 This is the first charge-discharge curve of the cathode material obtained in Comparative Example 3 of the present invention at 0.05C;
[0067] Figure 15 This is the first charge-discharge curve of the cathode material obtained in Comparative Example 4 of this invention at 0.05C;
[0068] Figure 16 This is a cycle performance diagram of the cathode material obtained in Example 1 of the present invention at 1C;
[0069] Figure 17 This is a graph showing the cycling performance of the cathode material obtained in Comparative Example 1 of this invention at 1C.
[0070] Figure 18 This is a graph showing the cycling performance of the cathode material obtained in Comparative Example 2 of this invention at 1C.
[0071] Figure 19 This is a graph showing the cycling performance of the cathode material obtained in Comparative Example 3 of this invention at 1C.
[0072] Figure 20 This is a graph showing the cycle performance of the cathode material obtained in Comparative Example 4 of this invention at 1C.
[0073] Figure 21 This is a rate performance diagram of the cathode material obtained in Example 1 of the present invention;
[0074] Figure 22 This is a rate performance diagram of the cathode material obtained in Comparative Example 1 of this invention;
[0075] Figure 23 This is a rate performance diagram of the cathode material obtained in Comparative Example 2 of this invention;
[0076] Figure 24 This is a rate performance diagram of the cathode material obtained in Comparative Example 3 of this invention;
[0077] Figure 25 This is a rate performance diagram of the cathode material obtained in Comparative Example 4 of this invention;
[0078] Figure 26 This is the first charge-discharge curve of the cathode material obtained in Example 2 of the present invention at 0.05C;
[0079] Figure 27 This is the first charge-discharge curve of the cathode material obtained in Example 3 of the present invention at 0.05C;
[0080] Figure 28 This is the first charge-discharge curve of the cathode material obtained in Example 4 of the present invention at 0.05C;
[0081] Figure 29This is a cycle performance diagram of the cathode material obtained in Example 2 of the present invention at 1C;
[0082] Figure 30 This is a cycle performance diagram of the cathode material obtained in Example 3 of the present invention at 1C;
[0083] Figure 31 This is a cycle performance diagram of the cathode material obtained in Example 4 of the present invention at 1C;
[0084] Figure 32 This is a rate performance diagram of the cathode material obtained in Example 2 of the present invention;
[0085] Figure 33 This is a rate performance diagram of the cathode material obtained in Example 3 of the present invention;
[0086] Figure 34 This is a rate performance diagram of the cathode material obtained in Example 4 of the present invention. Detailed Implementation
[0087] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0088] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.
[0089] Example 1:
[0090] 20.0160g FeSO4·7H2O and 6.8179g Na2SO4 were dispersed in 100mL of aqueous solution, and 1.2681g ascorbic acid was added. The mixture was sonicated at room temperature (20-35℃) for 30min to obtain a clear and transparent blue-green mixed solution. The inlet temperature of the spray drying equipment was set to 200℃, the fan frequency to 80Hz, the feed rate of the mixed solution to 400mL / h, and the needle passing rate to 5s / time. After the inlet temperature of the equipment reached a stable state of 200±5℃, the mixed solution was spray dried to obtain approximately 18g of white solid powder.
[0091] 9.5g of the above-mentioned white solid powder, 0.5g of multi-walled carbon nanotubes (i.e., their mass percentage is 5% of the total mass of the white solid powder and carbon matrix) and 50g of zirconium oxide balls were placed in a 100mL agate ball mill jar and ball-milled at 500r / min for 6h to obtain a cathode material precursor. The obtained cathode material precursor was transferred to a tube furnace and heated to 350℃ at 2℃ / min under a nitrogen atmosphere, and sintered at a constant temperature for 12h to obtain a black powdery solid, which is designated as composite polyanionic sodium ferrous sulfate cathode material 1. The analysis by an organic elemental analyzer showed that cathode material 1 includes active material and carbon matrix material, with a mass fraction of carbon matrix material of 7.24%, and the molecular formula of active material is Na4Fe3(SO4)5.
[0092] Figure 1 Here is a SEM image of the cathode material from Example 1. Figure 1 As can be seen from Figure a: the cathode material in this embodiment is composed of multiple small sodium ferrous sulfate particles and multi-walled carbon nanotubes, forming spherical secondary particles with a diameter of approximately 1-5 μm. Figure 1 As can be seen from b, sodium ferrous sulfate particles and multi-walled carbon nanotubes (i.e., carbon nanotubes marked in b) are uniformly distributed and in close contact, which can significantly improve the electronic conductivity of the cathode material.
[0093] Figure 6 This is the XRD pattern of Example 1. From Figure 6 As can be seen from the XRD characteristic diffraction peaks of the cathode material in Example 1 ( Figure 6 a) The diffraction peaks in the sample are in the same position as those in the standard card (PDF#21-1360) of Na2Fe(SO4)2, and the crystallinity is good.
[0094] Comparative Example 1:
[0095] 20.0160g FeSO4·7H2O7 and 6.8179g Na2SO4 were dispersed in 100mL of aqueous solution, and 1.2681g ascorbic acid was added. The mixture was sonicated at room temperature (20-35℃) for 30min to obtain a clear and transparent blue-green mixed solution. The inlet temperature of the spray drying equipment was set to 200℃, the fan frequency to 80Hz, the material feed rate to 400mL / h, and the needle passing rate to 5s / time. After the inlet temperature of the equipment reached a stable state of 200±5℃, the mixed solution was spray dried to obtain approximately 18g of white solid powder.
[0096] The white solid powder was transferred to a tube furnace and heated to 350°C at a rate of 2°C / min under a nitrogen atmosphere. The mixture was then sintered at a constant temperature for 12 hours to obtain a black powdery solid, which was designated as control cathode material 1.
[0097] Figure 2The SEM image of the comparative cathode material 1 in Comparative Example 1 is shown below. Figure 2 It can be seen that, compared to cathode material 1, it exhibits spherical secondary particles with a diameter of approximately 2-8 μm.
[0098] Figure 7 The image shows the XRD pattern of the comparative cathode material 1 in Comparative Example 1. From... Figure 7 As can be seen from the XRD characteristic diffraction peaks of the cathode material in Comparative Example 1 ( Figure 7 In example a), the diffraction peaks are in the same position as those on the Na2Fe(SO4)2 standard card (PDF#21-1360), but the degree of crystallinity is low. A comparison with Example 1 demonstrates that the introduction of a carbon matrix material can improve the crystallinity of the cathode material of this invention.
[0099] Comparative Example 2:
[0100] 20.0160g FeSO4·7H2O and 6.8179g Na2SO4 were dispersed in 100mL of aqueous solution. 1.2681g ascorbic acid and 0.9347g multi-walled carbon nanotubes were added. The mixture was sonicated at room temperature (20-35℃) for 30min to obtain a black suspension (the multi-walled carbon nanotubes were observed to agglomerate poorly). The inlet temperature of the spray dryer was set to 200℃, the fan frequency to 80Hz, the material feed rate to 400mL / h, and the needle passing rate to 5s / time. When the inlet temperature of the equipment reached a stable state of 200±5℃, the above black suspension was spray-dried under continuous and vigorous stirring to obtain a gray solid powder. The cathode material precursor obtained in the previous step was transferred to a tube furnace and heated to 350℃ at a nitrogen atmosphere at a rate of 2℃ / min. The mixture was sintered at a constant temperature for 12h to obtain a dark gray powdery solid, which was designated as control cathode material 2.
[0101] Figure 3 The SEM image of the comparative cathode material 2 in Comparative Example 2 is shown below. Figure 3 As can be seen from a, compared to cathode material 2, there is no obvious regular microstructure. Figure 3 As can be seen from b, the sodium ferrous sulfate particles do not have a tight contact with the multi-walled carbon nanotubes, and the multi-walled carbon nanotubes exhibit obvious aggregation, making it impossible to construct an effective electron and / or ion transport network.
[0102] Figure 8 The image shows the XRD pattern of the comparative cathode material 2 in Comparative Example 2. From... Figure 8 As can be seen from the XRD characteristic diffraction peaks of the cathode material in Comparative Example 2 ( Figure 8 a) has the same position as the diffraction peak of the Na2Fe(SO4)2 standard card (PDF#21-1360), but its impurity phase content is higher.
[0103] Comparative Example 3:
[0104] 7.2058g FeSO4·7H2O, 2.4544g Na2SO4, 0.3364g multi-walled carbon nanotubes and 50g zirconia balls were placed in a 100mL agate ball mill jar and ball-milled at 500r / min for 6h to obtain a cathode material precursor. The cathode material precursor was then transferred to a tube furnace and heated to 350℃ at 2℃ / min under a nitrogen atmosphere, and sintered at a constant temperature for 12h to obtain a black powdery solid, which was designated as control cathode material 3.
[0105] During the ball milling process, the material did not undergo dehydration treatment, resulting in severe adhesion to the mill wall and preventing the material from being mixed evenly. Figure 4 This is a SEM image of the comparative cathode material 3 in Comparative Example 3. From... Figure 4 As can be seen from a, the comparative cathode material 3 in Comparative Example 3 is composed of 1-2 μm spherical particles; from Figure 4 As can be seen from b, there are no multi-walled carbon nanotubes connecting the sodium ferrous sulfate particles, indicating that the material cannot be completely mixed uniformly, and electrons and / or ions cannot be effectively transported.
[0106] Figure 9 The image shows the XRD pattern of the comparative cathode material 3 in Comparative Example 3. From... Figure 9 As can be seen from the XRD characteristic diffraction peaks of the cathode material in Comparative Example 3 ( Figure 9 a) The positions of the diffraction peaks in the middle are consistent with those in the standard card (PDF#21-1360) of Na2Fe(SO4)2.
[0107] Comparative Example 4:
[0108] 12.0000g of FeSO4·7H2O was placed in a tube furnace and heated to 300℃ at a rate of 5℃ / min under a N2 atmosphere. After holding at this temperature for 10h, approximately 6.6g of anhydrous FeSO4 was obtained. 5.8550g of FeSO4, 3.6476g of Na2SO4, 0.5001g of multi-walled carbon nanotubes, and 50g of zirconia balls were weighed and placed in a 100mL agate ball mill jar. The mixture was ball-milled at 500r / min for 6h to obtain a cathode material precursor. The cathode material precursor was then transferred to a tube furnace and heated to 350℃ at a rate of 2℃ / min under a nitrogen atmosphere. After holding at this temperature for 12h, a black powdery solid was obtained, designated as control cathode material 4.
[0109] Figure 5 For the comparative cathode material 4 of Comparative Example 4, SEM images are shown below. Figure 5 As can be seen from a, compared to cathode material 4, which consists of secondary particles composed of numerous tiny sodium ferrous sulfate particles; from Figure 5As can be seen from b, the sodium ferrous sulfate particles are in close contact with the multi-walled carbon nanotubes, and the multi-walled carbon nanotubes are relatively evenly distributed, enabling the simultaneous transfer of electrons and ions.
[0110] Figure 10 The image shows the XRD pattern of the comparative cathode material 4 in Comparative Example 4. From... Figure 10 As can be seen from the XRD characteristic diffraction peaks of the cathode material in Comparative Example 4 ( Figure 10 In (a) the diffraction peaks of the sample are in the same position as those of the Na2Fe(SO4)2 standard card (PDF#21-1360), but the impurity phase content is also relatively high. This is because some of the Fe2Fe ... 2+ Oxidized to Fe 3+ Elemental analysis of cathode material 1 and control cathode materials 1-4 was performed using an organic elemental analyzer (model: vario EL CUBE; manufacturer: elementar, Germany). The mass contents of Na, Fe, S, C, etc. are listed in Table 1.
[0111] Table 1 Elemental content of cathode materials
[0112] Cathode material 1 9.76 18.81 19.49 7.24 Comparison of cathode material 1 9.77 18.99 21.36 1.85 Comparison with cathode material 2 9.74 22.23 20.47 6.43 Comparison of cathode material 3 10.18 21.22 20.05 5.69 Comparison with cathode material 4 8.98 22.51 20.35 5.37
[0113] As shown in Table 1 and the SEM images, the cathode material prepared by the method of the present invention has a higher carbon content and the sodium ferrous sulfate particles are more uniformly distributed in the carbon nanotubes; while the cathode materials of Comparative Examples 1-4, especially Comparative Example 2, have low carbon content. This proves that the carbon matrix material faces a serious carbon retention problem during the spray drying process.
[0114] Application Example 1
[0115] The specific steps for preparing the positive electrode are as follows:
[0116] The positive electrode materials of Example 1 and Comparative Examples 1-4 were taken respectively, and the positive electrode material, acetylene black and polyvinylidene fluoride were dispersed in N-methylpyrrolidone solvent at a mass ratio of 8:1:1 and mixed thoroughly to form a slurry. The slurry was uniformly coated onto aluminum foil, dried under vacuum at 120°C, and then cut to obtain positive electrode sheets, which were respectively labeled as positive electrode sheet 1, comparative electrode sheet 1, comparative electrode sheet 2, comparative electrode sheet 3 and comparative electrode sheet 4.
[0117] Assemble the 2016 button cell: Take positive electrode 1, comparison electrode 1, comparison electrode 2, comparison electrode 3 and comparison electrode 4 respectively, pure Na sheet as negative electrode, polypropylene separator to separate positive and negative electrodes, 0.6M NaPF6 / PC / EMC / FEC as electrolyte, stainless steel shell as outer shell, assemble into 2016 button cell, and label them as battery 1, comparison battery 1, comparison battery 2, comparison battery 3 and comparison battery 4 respectively.
[0118] Test Example 1
[0119] 1. Charge / discharge performance test: Battery 1 and control batteries 1-4 were charged at room temperature, 2.0-4.5V (vs. Na). + Charge-discharge tests were conducted within the / Na) potential range at a current density of 0.05C. The test results are detailed below. Figure 11-15 .
[0120] like Figure 11-15 As shown, at 0.05C, the first-cycle discharge specific capacity of the cathode material in Example 1 can reach 87.45 mAh g⁻¹. -1 It is significantly better than Comparative Example 1 ( Figure 12 80.50mAh g -1 Comparative Example 2 Figure 13 69.50mAh g -1 Comparative Example 3 Figure 14 64.89mAh g -1 ) and Comparative Example 4 ( Figure 15 69.90mAh g -1 The first-week discharge specific capacity.
[0121] 2. Cycle stability and capacity retention: Battery 1 and control batteries 1-4 were tested at room temperature, 2.0-4.5V (vs. Na). + Charge-discharge tests were conducted within the / Na) potential range at a current density of 1C. The test results are detailed below. Figure 16-20 .
[0122] like Figure 16 In Example 1, the composite polyanionic sodium ferrous sulfate cathode material prepared by coupling spray drying with solid-phase ball milling and low-temperature pyrolysis showed the best cycling stability at 1C, with a capacity retention of up to 98.76% after 200 cycles; the discharge specific capacity was approximately 80 mAh g. -1 Comparative Example 1 (see Figure 17 The capacity retention rate is 98.59%; the discharge specific capacity is approximately 45 mAh g. -1 Comparative Example 2 (see Figure 18 The capacity retention rate is 88.42%; the discharge specific capacity is approximately 35 mAh g. -1 Comparative Example 3 (see Figure 19 The capacity retention rate is 94.67%; the discharge specific capacity is approximately 60 mAh g. -1 ) and Comparative Example 4 (see Figure 20 The capacity retention rate is 95.54%; the discharge specific capacity is approximately 65 mAh g. -1Under the same test conditions, the discharge specific capacity, cycle stability and capacity retention are far inferior to those of Example 1.
[0123] 3. Rate test: Battery 1 and control batteries 1-4 were tested at room temperature, 2.0-4.5V (vs. Na). + Within the / Na) potential range, the battery was first activated by performing two cycles of rate charge-discharge at a current density of 0.05C. Subsequently, rate charge-discharge tests were performed sequentially at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 4C, 5C, and 1C (five cycles at each current density). The rate discharge test results for battery 1 and comparison batteries 1-4 are shown in [reference needed]. Figure 21-25 , Figure 21 For the rate performance of the cathode material in Example 1, battery 1 exhibits better rate performance under 5C charge-discharge conditions, with a discharge specific capacity of 42.78 mAh g⁻¹. -1 In contrast, batteries 1-4, under 5C charge / discharge conditions, all exhibit a discharge specific capacity of less than 37 mAh g. -1 .
[0124] The above tests show that the cathode material prepared by the present invention through the coupling of spray drying, solid-phase mixing and low-temperature pyrolysis reaction process enhances the interaction between the three raw materials and can significantly improve the electrochemical performance of the cathode material.
[0125] Example 2:
[0126] 20.0160g FeSO4·7H2O and 5.1134g Na2SO4 were dispersed in 100mL of aqueous solution, and 1.2681g ascorbic acid was added. The solution was sonicated at room temperature (20-35℃) for 30min to obtain a clear and transparent blue-green solution. A spray dryer was set with an inlet temperature of 200℃, a fan frequency of 80Hz, a material feed rate of 400mL / h, and a needle-passing rate of 5s / pass. Once the inlet temperature reached a stable state of 200±5℃, the prepared blue-green solution was spray-dried to obtain a white solid powder. 9.5g of the obtained white solid powder and 0.5g of multi-walled carbon nanotubes (the mass of which is the white solid powder and carbon matrix) were then mixed. 5% of the total mass of zirconia balls (50g) were placed in a 100mL agate ball mill jar and milled at 500r / min for 6h to obtain a cathode material precursor. The cathode material precursor obtained in the previous step was transferred to a tube furnace and heated to 350℃ at 2℃ / min under a nitrogen atmosphere and held at that temperature for 12h to obtain a black powdery composite polyanionic sodium ferrous sulfate cathode material 2. The analysis by an organic elemental analyzer showed that the cathode material included an active material and a carbon matrix material, with a mass fraction of 7.20% for the carbon matrix material and a molecular formula of Na2Fe2(SO4)3 for the active material.
[0127] Example 3:
[0128] 20.0160g FeSO4·7H2O and 10.2269g Na2SO4 were dispersed in 100mL of aqueous solution, and 1.2681g ascorbic acid was added. The solution was sonicated at room temperature (20-35℃) for 30min to obtain a clear and transparent blue-green solution. A spray dryer was set with an inlet temperature of 200℃, a fan frequency of 80Hz, a material feed rate of 400mL / h, and a needle-passing rate of 5s / pass. Once the inlet temperature reached a stable state of 200±5℃, the prepared blue-green solution was spray-dried to obtain a white solid powder. 9.5g of the obtained white solid powder and 0.5g of multi-walled carbon nanotubes (the mass of which is the white solid powder and carbon-based components) were then combined. 5% of the total mass of the positive electrode material and 50g of zirconium oxide balls were placed in a 100mL agate ball mill jar and ball milled at 500r / min for 6h to obtain a positive electrode material precursor. The positive electrode material precursor obtained in the previous step was transferred to a tube furnace and heated to 350℃ at 2℃ / min under a nitrogen atmosphere and held at the temperature for 12h to obtain a black powdery composite polyanionic sodium ferrous sulfate positive electrode material 3. The analysis by an organic element analyzer showed that the positive electrode material included active material and carbon matrix material, the mass fraction of carbon matrix material was 7.09%, and the molecular formula of active material was Na2Fe(SO4)2.
[0129] Example 4:
[0130] 20.0160g FeSO4·7H2O and 6.1361g Na2SO4 were dispersed in 100mL of aqueous solution, and 1.2681g ascorbic acid was added. The solution was sonicated at room temperature (20-35℃) for 30min to obtain a clear and transparent blue-green solution. A spray dryer was set with an inlet temperature of 200℃, a fan frequency of 80Hz, a material feed rate of 400mL / h, and a needle-passing rate of 5s / pass. Once the inlet temperature reached a stable state of 200±5℃, the prepared blue-green solution was spray-dried to obtain a white solid powder. 9.5g of the obtained white solid powder and 0.5g of multi-walled carbon nanotubes (the mass of which is the white solid powder and carbon matrix) were then mixed. 5% of the total mass of zirconium oxide balls (50g) were placed in a 100mL agate ball mill jar and milled at 500r / min for 6h to obtain a cathode material precursor. The cathode material precursor obtained in the previous step was transferred to a tube furnace and heated to 350℃ at 2℃ / min under a nitrogen atmosphere and held at that temperature for 12h to obtain a black powdery composite polyanionic sodium ferrous sulfate cathode material 4. The analysis by an organic elemental analyzer showed that the cathode material included an active material and a carbon matrix material. The mass fraction of the carbon matrix material was 7.48%, and the molecular formula of the active material was Na6Fe5(SO4)8.
[0131] The cathode materials obtained in Examples 2-4 have basic properties as follows: Figure 1The spherical secondary particles shown are uniformly distributed with sodium ferrous sulfate particles and multi-walled carbon nanotubes, and the two are in close contact; the XRD pattern of the cathode material is basically the same as... Figure 6 The a-value is consistent and has good crystallinity.
[0132] Application Example 2
[0133] The composite polyanionic sodium ferrous sulfate cathode materials of Examples 2-4 were used to prepare cathode plates and batteries according to Application Example 1, and were respectively denoted as cathode plate 2-4 and battery 2-4.
[0134] Test Example 2
[0135] Following the test method in Test Example 1, the electrochemical performance of batteries 2-4 was tested respectively. The test results are shown in [reference 1]. Figure 26-34 The test data for batteries 1-4 are summarized in Table 2.
[0136] Table 2 Electrochemical performance of batteries 1-4
[0137] Battery 1 <![CDATA[87.45mAh g -1 ]]> 200 laps 98.76% <![CDATA[42.78mAh g -1 ]]> Battery 2 <![CDATA[82.28mAh g -1 ]]> 200 laps 100% <![CDATA[38.35mAh g -1 ]]> Battery 3 <![CDATA[79.63mAh g -1 ]]> 200 laps 100% <![CDATA[50.18mAh g -1 ]]> Battery 4 <![CDATA[65.09mAh g -1 ]]> 200 laps 100% <![CDATA[42.10mAh g -1 ]]>
[0138] As shown in Table 2, batteries 1-4 all exhibited excellent cycle stability (after 200 cycles at 1C current density, their capacity retention rate all exceeded 95%) and rate performance electrochemical performance (at 5C current density, their discharge specific capacity could maintain more than 50% of the discharge specific capacity at 1C current density, and after switching from 5C current density to 1C current density, their discharge specific capacity was basically the same as the capacity at the original 1C current density). This proves that the process of coupling spray drying with solid-phase mixing and low-temperature pyrolysis reaction of the present invention has strong universality, and the prepared cathode material has constructed an effective electron and / or ion transport network, which can achieve effective electron and / or ion transport.
[0139] The exemplary embodiments of the present invention have been described above. However, the scope of protection of this application is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a composite polyanionic sodium ferrous sulfate cathode material, characterized in that, The composite polyanionic sodium ferrous sulfate cathode material comprises an active material and a carbon matrix material, wherein the molecular formula of the active material is Na. x Fe y (SO4) z , where x+2y=2z, and the ratio of x:y:z is 2-6:1-5:2-8; The preparation method is a coupling process of spray drying, solid-phase mixing, and high-temperature pyrolysis reaction, including the following steps: S1: Sodium sulfate and ferrous sulfate are uniformly dissolved in water, an antioxidant is added, and the mixture is ultrasonically treated to obtain a mixed solution; in the mixed solution, Fe... 2+ The concentration was 0.001-0.4 kg / L, and Na + Fe 2+ and SO4 2- The molar ratio of the antioxidant to ferrous sulfate is 2-6:1-5:2-8; the molar ratio of the antioxidant to ferrous sulfate is 0.01-0.5:
1. S2: The mixed solution obtained in step S1 is spray-dried to obtain a solid powder, wherein the Na and Fe metal salts in the solid powder are highly dispersed at the atomic level; the outlet temperature of the spray dryer is 100-150 ℃; the feed rate of the mixed solution during the spray drying process is 200-2000 mL / h. S3: The solid powder obtained in step S2 is mixed with the carbon matrix material through solid-state mixing to obtain a cathode material precursor; the carbon matrix material accounts for 1-10 wt% of the total mass of the cathode material precursor; the solid-state mixing is ball milling, and the conditions for ball milling include: ball milling time of 1-10 h; ball milling speed of 200-800 rpm; S4: The cathode material precursor obtained in step S3 is subjected to high-temperature pyrolysis under oxygen-free conditions to obtain a composite polyanionic sodium ferrous sulfate cathode material; the conditions for high-temperature pyrolysis include: pyrolysis at a pyrolysis temperature of 350-400 ℃ for 12-24 h.
2. The preparation method according to claim 1, characterized in that, In step S1, the ferrous sulfate is selected from ferrous sulfate or ferrous sulfate hydrate; In step S1, the antioxidant is selected from at least one of ascorbic acid and its salts, isoascorbic acid and its salts.
3. The preparation method according to claim 1, characterized in that, In step S2, the solid powder is white.
4. The preparation method according to claim 1, characterized in that, In step S3, the carbon matrix material is inorganic carbon; The cathode material precursor is a black powdery solid.
5. The preparation method according to claim 1, characterized in that, In step S4, the oxygen-free condition is an inert atmosphere; The inert atmosphere is an inert gas.
6. The composite polyanionic sodium ferrous sulfate cathode material obtained by the preparation method according to any one of claims 1-5; The composite polyanionic sodium ferrous sulfate cathode material comprises an active material and a carbon matrix material, wherein the molecular formula of the active material is Na. x Fe y (SO4) z , where x+2y=2z, and the ratio of x:y:z is 2-6:1-5:2-8; In the cathode material, the mass fraction of the carbon matrix material is 1-10 wt%.
7. A positive electrode sheet, characterized in that, The positive electrode sheet comprises the positive electrode material as described in claim 6.
8. The application of the positive electrode material of claim 6 or the positive electrode sheet of claim 7 in a sodium-ion battery.
9. A sodium-ion battery, the sodium-ion battery comprising the positive electrode material of claim 6 or the positive electrode sheet of claim 7.
Citation Information
Patent Citations
Na2Fe(SO4)2 / C electrode material jointly prepared by graphene and / or acetylene black, preparation method thereof and prepared battery
CN110336021A